The Effect of the Thermosensitive Biodegradable PLGA⁻PEG⁻PLGA Copolymer on the Rheological, Structural and Mechanical Properties of Thixotropic Self-Hardening Tricalcium Phosphate Cement - Vojtova, Lucy; Michlovska, Lenka; Valova, Kristyna; Zboncak, Marek; Trunec, Martin; Castkova, Klara; Krticka, Milan; Pavlinakova, Veronika; Polacek, Petr; Dzurov, Matej; Lukasova, Vera; Rampichova, Michala; et al. (International journal of molecular sciences, 2019)
The current limitations of calcium phosphate cements (CPCs) used in the field of bone regeneration consist of their brittleness, low injectability, disintegration in body fluids and low biodegradability. Moreover, no method is currently available to measure the setting time of CPCs in correlation with the evolution of the setting reaction. The study proposes that it is possible to improve and tune the properties of CPCs via the addition of a thermosensitive, biodegradable, thixotropic copolymer based on poly(lactic acid), poly(glycolic acid) and poly(ethylene glycol) (PLGA⁻PEG⁻PLGA) which undergoes gelation under physiological conditions. The setting times of alpha-tricalcium phosphate (α-TCP) mixed with aqueous solutions of PLGA⁻PEG⁻PLGA determined by means of time-sweep curves revealed a lag phase during the dissolution of the α-TCP particles. The magnitude of the storage modulus at lag phase depends on the liquid to powder ratio, the copolymer concentration and temperature. A sharp increase in the storage modulus was observed at the time of the precipitation of calcium deficient hydroxyapatite (CDHA) crystals, representing the loss of paste workability. The PLGA⁻PEG⁻PLGA copolymer demonstrates the desired pseudoplastic rheological behaviour with a small decrease in shear stress and the rapid recovery of the viscous state once the shear is removed, thus preventing CPC phase separation and providing good cohesion. Preliminary cytocompatibility tests performed on human mesenchymal stem cells proved the suitability of the novel copolymer/α-TCP for the purposes of mini-invasive surgery.
Keywords: polyestery; polyethylenglykoly; viabilita buněk; injectable bone cements; Mechanical Phenomena; polyglactin 910; biocompatibility; rheology; kultivované buňky; biokompatibilní materiály; Bone Cements; Humans; Materials Testing; Rheology; Molecular Structure; morphology; Biocompatible Materials; molekulární struktura; testování materiálů; Polymerization; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; Polyethylene Glycols; kostní cementy; Cells, Cultured; kinetics; Calcium Phosphates; mechanické jevy; Polyesters; Cell Survival; lidé; Polyglactin 910; reologie; polymerizace; fosforečnany vápenaté; thixotropic